2019
DOI: 10.1109/tps.2018.2879604
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Shielding Design of Infrared Imaging Video Bolometer for LHD Deuterium Experiment

Abstract: InfraRed imaging Video Bolometer (IRVB) is a powerful diagnostic for the plasma radiation measurement. Study on plasma radiation phenomena, e.g., plasma detachment is one of the crucial issues to realize a fusion reactor. In order to apply the IRVB to such a study, a shielding is required to protect an IR camera from neutron irradiation. In the Large Helical Device (LHD) deuterium experiment has started in 2017. Then, the shielding was designed using MCNP6 code with the threedimensional modelling of LHD. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The validity and the details regarding the shielding adopted in the present study are well reported in Ref. [14]. The temperature calibration was performed before the LHD experiment campaign by using blackbody calibration source with known emissivity and temperature.…”
Section: Divertor Arrangement and Ir Thermography In Lhdmentioning
confidence: 93%
“…The validity and the details regarding the shielding adopted in the present study are well reported in Ref. [14]. The temperature calibration was performed before the LHD experiment campaign by using blackbody calibration source with known emissivity and temperature.…”
Section: Divertor Arrangement and Ir Thermography In Lhdmentioning
confidence: 93%
“…e main disadvantage of the EM algorithm is that it may converge to a local extremum. Fuzzy C-means clustering is computationally expensive [15]. Comprehensive comparison, the K-means clustering algorithm is more suitable for infrared thermal imaging images.…”
Section: Image Segmentation Clustering Segmentation Algorithmmentioning
confidence: 99%
“…. m) is the sample point in R d , then the mean shift vector at point x can be defined as equation (15), T l is a high-dimensional spherical area with a radius of l, and satisfies the equation (15). w means that out of the m sample points, w fall into the T l area.…”
Section: Infrared Ermal Imaging Target Recognition and Trackingmentioning
confidence: 99%
“…As the result of preliminary measurement in GAMMA10/PDX, temperature rise on the foil absorber was up to 1/5 of LHD. In LHD [11], 𝜎 ! "#$ is 1200 µW/cm 2 without time averaging and signal-to-noise ratio, 𝑆𝑁𝑅 1232 in TABLE II of [12], is 3.4.…”
Section: B Sensitivity Of Irvbmentioning
confidence: 99%